2014
DOI: 10.4172/2329-8790.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Targetting therapy of A20 Mouse Lymphoma model using Anti CD-138 Antibody conjugated Gold Nanospheres

Abstract: The aim of this study was to investigate the therapeutic effects of photothermal targeting of hollow gold nanospheres on lymphoma. Hollow gold nanospheres were modified by PEG (polyethylene glycol) and conjugated to anti-CD138 antibody. The conjugates were then injected into the A20 mouse lymphoma model followed by nearinfrared laser radiation (NIR). By examining the level of immunoglobulin G2a secreted by A20 cells and measuring the weight of specimen biopsy, tumorgenesis was determined. Finally, the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It should be noted that anti-CD138-Ab exhibited more selectively toward A20 cells than R-Ab, and the tunable band for hollow AuNPs was 520-950 nm. These findings indicated that anti-CD138-Ab-PEG-AuNPs could be used for PTT-based lymphoma treatment[96].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…It should be noted that anti-CD138-Ab exhibited more selectively toward A20 cells than R-Ab, and the tunable band for hollow AuNPs was 520-950 nm. These findings indicated that anti-CD138-Ab-PEG-AuNPs could be used for PTT-based lymphoma treatment[96].…”
mentioning
confidence: 80%
“…It should be noted that the anti-CD33 antibody already got approval for AML treatment [95]; therefore, CD33-Ab-PEG-GNR could be used to treat AML. [96] loaded anti-CD138 antibody (anti-CD138-Ab) on the surface of PEG-modified hollow AuNPs (anti-CD138-Ab-PEG-AuNPs) that selectively target A20 lymphoma cells. Treatment of female BALB/c mice with anti-CD138-Ab-PEG-AuNPs followed by NIR treatment (after 24 h) significantly decreased lymphoma growth and IgG2a expression at 4 days compared to a control.…”
Section: Photothermal Therapymentioning
confidence: 99%
See 1 more Smart Citation